2017
DOI: 10.1002/chem.201703687
|View full text |Cite
|
Sign up to set email alerts
|

Switching of Reaction Pathway from C−C Rollover to C−N Ring‐Extension Annulation

Abstract: This work discloses that a simple change in the anion of a copper(II) reagent along with the reaction solvent can dramatically alter the course of a Cp*Rh -catalyzed C-H activation-annulation reaction leading to completely switchable chemoselective products. The nature of the anion in terms of its coordinating ability and basicity, and also the polarity of the solvent have been found to be the crucial factors in the observed divergence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 60 publications
1
20
0
Order By: Relevance
“…In contrast, the synthesis of 1‐alkoxy‐isochromenes catalysed by Ag I complexes with a pyridine‐containing macrocyclic ligand, gives lower yields in the presence of slightly more coordinating counterions than tetrafluoroborate, such as triflate or triflimidate . Other authors have observed that the tetrafluoroborate anion, with a lower coordinating ability than triflate, favours the formation of a cationic complex and enhances the electrophilicity of Rh that triggers insertion processes of a coordinated alkyne …”
Section: Coordinating Ability Indicesmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the synthesis of 1‐alkoxy‐isochromenes catalysed by Ag I complexes with a pyridine‐containing macrocyclic ligand, gives lower yields in the presence of slightly more coordinating counterions than tetrafluoroborate, such as triflate or triflimidate . Other authors have observed that the tetrafluoroborate anion, with a lower coordinating ability than triflate, favours the formation of a cationic complex and enhances the electrophilicity of Rh that triggers insertion processes of a coordinated alkyne …”
Section: Coordinating Ability Indicesmentioning
confidence: 99%
“…[40] Other authors have observed that the tetrafluoroborate anion,w ith al ower coordinating ability than triflate, favours the formation of acationic complex and enhances the electrophilicity of Rh that triggers insertion processes of acoordinated alkyne. [41] Ac atalytic hydrosilylation of n-octenet akes place with an in-situ generated catalyst that results from mixing[ Co(acac) 2 ] and ac helating or pincerN -o rP -donor ligand. In this reaction, much better yields and higher selectivity toward the branched product than to the linear one are obtainedw hen it is carried out in hexane or toluene, rather than in THF,atrend that has been associatedt ot he poorer coordinationa bilities of hexane and toluene.…”
Section: Reactivity and Catalysismentioning
confidence: 99%
“…Chemodivergent reactions are interesting and efficient protocols that form the structurally different heterocyclic compounds from the same starting materials through simple change of reaction conditions [1,2,3,4,5,6,7,8,9,10]. Among them, the solvent-dependent or solvent-controlled chemodivergent reactions have been well applied in the synthesis of heterocyclic compounds [11,12,13,14,15,16,17,18,19,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…A recent addition to the existing strategies is “rollover C–H activation” protocol, 2 the catalytic version of which has been applied successfully to functionalize strongly chelating (bidentate/tridentate) organic molecules. 3 The basic problem associated with rollover C–H activation in chelating molecules is facile formation of a stable metallachelate, which is resistant to reopen via decomplexation, thus inhibiting the activation of the C–H bond (Figure 1a). Hence, examples of successful catalytic protocols involving rollover C–H activation functionalization are still limited.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, examples of successful catalytic protocols involving rollover C–H activation functionalization are still limited. 3 These include C–H cyanation of arylimidazo[1,2-α]pyridines (by the Song and Hao group), 3a C–H diamination of arylpyridines (by the Lu group) 3b and purines (by the Chang group), 3c and annulation of 2-phenylimidazo[1,2- a ]pyridines (by the Li group). 3d Later, the Chang group developed elegant protocols for rollover functionalization of pyridine ligand-based strong bidentate (2,2′-bipyridines) and tridentate (2,2′:6′,2″-terpyridines) molecules.…”
Section: Introductionmentioning
confidence: 99%